Using Artificial Immune Systems to Sort and Shim Insertion Devices at Diamond Light Source. Issue 1 (1st December 2022) - Whittle, Joss; Basham, Mark; Patel, Zena; Rial, Edward; Oates, Robert; Moazzam, Yousef
Abstract: This work presents the Opt-ID software developed by the Rosalind Franklin Institute (RFI) and Diamond Light Source (DLS) in collaboration with Helmholtz-Zentrum Berlin (HZB). Opt-ID allows for efficient simulation of synchrotron Insertion Devices (ID) and the B fields produced by a given arrangement of candidate magnets. It provides an optimization framework built on the Artificial Immune System (AIS) algorithm for swapping and adjusting magnets within an ID to observe how these changes would affect the magnetic field of a real-world device, guiding ID builders in the steps they should take during ID tuning. Code for Opt-ID is provided open-source under the Apache-2.0 License on Github: https://github.com/rosalindfranklininstitute/Opt-ID